2013
DOI: 10.5251/ajfn.2013.3.3.122.126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of micronutrient potentials of seven commonly consumed indigenous spices from Nigeria

Abstract: Micronutrient deficiencies remain a public health challenge globally, especially among developing countries of the world. Spices constitute an important part of daily diets of many populations but their nutritional roles are yet to be fully investigated. Micronutrient potentials of seven indigenous spices in Nigeria (Allium Ascalonicum, Piper guneensis, Aframomum melegueta, Zingiber officinale, Ocimum basilicum, Allium sativum, and Eugenia caryophyllata) were evaluated using standard methods of AOAC and atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…In 21,22 , and are different from values reported by other researchers 23 . The observed differences in values could be as a result of seasonal and geographic variations; as these samples were obtained from different geographic locations and years.…”
Section: Discussioncontrasting
confidence: 62%
“…In 21,22 , and are different from values reported by other researchers 23 . The observed differences in values could be as a result of seasonal and geographic variations; as these samples were obtained from different geographic locations and years.…”
Section: Discussioncontrasting
confidence: 62%
“…Spices have been considered a good source of micronutrients [ 50 ]. However, in the present study, any significant difference was observed between control and the spiced groups.…”
Section: Discussionmentioning
confidence: 99%
“…From time immemorial, spices have been reportedly used in Nigeria to prepare 'pepper soups', in the diets of post-partum women to aid contraction of the uterus, as food seasoning, as well as in the preparation of a meat sauce called Yaji (Omotayo, 2013). Yaji, also called suya sauce is a local meat sauce made from complex spices and other additives.…”
Section: Introductionmentioning
confidence: 99%